Impact of microplastics and ocean acidification on critical stages of sea urchin (Paracentrotus lividus) early development - Juan Ignacio Bertucci; Juan Bellas (Chemosphere, 2022)
One of the major consequences of increasing atmospheric CO2 is a phenomenon known as ocean acidification. This alteration of water chemistry can modulate the impact on marine organisms of other stressors also present in the environment, such as microplastics (MP). The objective of this work was to determine the combined impact of microplastic pollution and ocean acidification on the early development of Paracentrotus lividus. To study these multi-stressor impacts on development P. lividus the sea urchin embryo test (SET) was used. Newly fertilised embryos of P. lividus were exposed to a control treatment (filtered natural seawater), MP (3000 particles/mL), acidified sea water (pH = 7.6), and a combination of MP and acidification (3000 particles/mL + pH = 7.6). After 48, 72, and 96 h measurements of growth and morphometric parameters were taken. Results showed that ocean acidification and MP cause alterations in growth and larval morphology both before and after the larvae start to feed exogenously. The exposure to MP under conditions of ocean acidification did not produce any additional effect on growth, but differences were observed at the morphological level related to a decrease in the width of larvae at 48 h. Overall, changes in larvae shape observed at three key points of their development could modify their buoyancy affecting their ability to obtain and ingest food. Therefore, ocean acidification and MP pollution might compromise the chances of P. lividus to survive in the environment under future scenarios of global climate change.